Hyperintense acute reperfusion marker on FLAIR in posterior circulation infarction - Förster, Alex; Wenz, Holger; Böhme, Johannes; Al-Zghloul, Mansour; Groden, Christoph (PLOS ONE, 2016)
Purpose In the present study, we aimed to investigate the frequency of blood brain barrier injury in posterior circulation infarction as demonstrated by the hyperintense acute reperfusion marker (HARM) on fluid attenuated inversion recovery images (FLAIR). Methods From a MRI report database we identified patients with posterior circulation infarction who underwent MRI, including perfusion-weighted images (PWI), within 12 hours after onset and follow-up MRI within 24 hours and analyzed diffusion-weighted images (DWI), PWI, FLAIR, and MR angiography (MRA). On FLAIR images, the presence of HARM was noted by using pre-specified criteria (focal enhancement in the subarachnoid space and/or the ventricles). Results Overall 16 patients (median age of patients 68.5 (IQR 55.5-82.75) years) with posterior circulation infarction were included. Of these, 13 (81.3%) demonstrated PCA occlusion, and 3 (18.7%) patients BA occlusion on MRA. Initial DWI demonstrated ischemic lesions in the thalamus (68.8%), splenium (18.8%), hippocampus (75%), occipital lobe (81.3%), mesencephalon (18.8%), pons (18.8%), and cerebellum (50%). On follow-up MRA recanalization was noted in 10 (62.5%) patients. On follow-up FLAIR images, HARM was observed in 8 (50%) patients. In all of these, HARM was detected remote from the acute ischemic lesion. HARM was more frequently observed in patients with vessel recanalization (p = 0.04), minor infarction growth (p = 0.01), and smaller ischemic lesions on follow-up DWI (p = 0.05). Conclusions HARM is a frequent finding in posterior circulation infarction and associated with vessel recanalization, minor infarction growth as well as smaller infarction volumes in the course. Neuroradiologists should be cognizant of the fact that HARM may be present on short interval follow-up FLAIR images in patients with acute ischemic infarction who initially underwent MRI and received intravenous gadolinium-based contrast agents.
Gesehen am 17.06.2019